The Wind Effect on Biogeochemistry in Eddy Cores in the Northern South China Sea - Chow, Chun Hoe; Shih, Yung-Yen; Chien, Ya-Tang; Chen, Jing Yi; Fan, Ning; Wu, Wei-Chang; Hung, Chin-Chang (Frontiers in Marine Science, 2021)
Cyclonic and anticyclonic eddies are usually characterized by upwelling and downwelling, respectively, which is induced by eddy pumping near their core. Using repeated expendable-bathythermograph transect (XBT), Argo floats and cruise experiments we determined that not all eddies in the northern South China Sea (NSCS) were accompanied by eddy pumping. The weakening of background thermocline was attributed to the strengthening of eddy pumping, affected by 1) the wind-induced meridional Sverdrup transports and 2) the Kuroshio intrusion into the NSCS. Higher particulate-organic-carbon (POC) fluxes (> 100 mg-C m-2 d-1) were found near the eddy cores with significant eddy pumping (defined by a depth change of 22oC isotherm near the thermocline for over 10 m), although the satellite-estimated POC fluxes were inconsistent with the in-situ POC fluxes. The nitrogen-limitation transition and high POC flux were even found near the core of a smaller mesoscale (diameter < 100 km) cyclonic eddy in May 2014, during the weakening of the background thermocline in the NSCS. This finding provides evidence that small mesoscale eddies can efficiently provide nutrients to the subsurface, and can remove carbon from the euphotic zone. This is important for global warming which generally strengthens the upper-ocean stratification.